Liseuse from the periphery - Juneja, Monica (Materialized histories, 2021)
PDF I discovered this enticing, unusual figurine of a young woman absorbed in reading a book in the souvenir section of New Delhi’s Cottage Industries Emporium - a sprawling, ethni-cally designed store created as an outlet for India’s prolific ‘craft’ production. While looked upon with condescension by the local intelligentsia, the emporium is a favorite […]